2021
DOI: 10.1371/journal.pone.0255166
|View full text |Cite
|
Sign up to set email alerts
|

Environmental non-governmental organizations and air-pollution governance: Empirical evidence from OECD countries

Abstract: Based on the panel data of environmental Non-Governmental Organizations (ENGOs) and air pollution in OECD countries, this paper uses econometric model to investigate the governance effect of ENGOs on air pollution. The results show that: ENGOs have a positive impact on the improvement of environmental quality, and the results are still valid after a series of robustness tests; Further mechanism analysis found that the environmental improvement by ENGOs is mainly achieved by increasing investment in environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Thirdly, the third sectors, companies and the public should be encouraged in air protection. Some empirical analyses have been shown that Environmental Non-Governmental Organizations (ENGOs) and companies have a positive impact on the improvement of environmental quality (Bao et al, 2020;Li et al, 2021). Local people can be mobilized and organized by ENGOs and companies to participate in environmental improvement activities , which will alleviate the pressure of governments on environmental protection.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the third sectors, companies and the public should be encouraged in air protection. Some empirical analyses have been shown that Environmental Non-Governmental Organizations (ENGOs) and companies have a positive impact on the improvement of environmental quality (Bao et al, 2020;Li et al, 2021). Local people can be mobilized and organized by ENGOs and companies to participate in environmental improvement activities , which will alleviate the pressure of governments on environmental protection.…”
Section: Discussionmentioning
confidence: 99%
“…6 For detailed information on the interviews, see Section 4, Empirical Analysis, below, and Online Appendix Part B. 7 Moreover, we included information on the number of environmental non-governmental organizations (ENGOs) per capita (Li et al, 2021). The data on ENGOs, however, is only available from the year 2000 onwards and thus might slightly distort our analysis.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…As shown in Figs 4 and 5 , increasing ENGOs participation level and right space will encourage local government to reach an evolutionarily stable state more quickly. Previous studies have shown that local ENGOs play a crucial role in local environmental governance [ 48 ], they achieve environmental improvements through increased investment in environmental protection [ 49 ], but sufficient space for political opportunities is needed for them to mobilize and organize public participation in environmental governance [ 50 ]. Accordingly, to achieve better effects in the multiple governance of agricultural non-point source pollution, local government should encourage more ENGOs to participate in the governance of agricultural non-point source pollution as well as improve the right space of local ENGOs.…”
Section: Numerical Simulationmentioning
confidence: 99%